BACTERIAL CONTAMINATION OF THE SURGICAL WOUND IN PATIENTS WITH STRANGULATED POSTOPERATIVE VENTRAL HERNIAS - Abdullajanov B.R; Isakov P.M. (Scholar Express Journals, 2023)
One of the topical issues of modern allohernioplasty is the prevention of the development of wound complications, among which are the formation of infiltrates, seroma, wound suppuration, dislocation of the prosthesis and relapse of the disease.
Keywords: disease; topical; complications